Violence against women in Japan: a review of recent trends and the implications of victimization survey results - Tsushima, Masahiro (Law and culture in Japan, 2025)
Purpose: This chapter examines violence against women in Japan. It illustrates how data obtained from victimization surveys can be employed to facilitate research. Methodology/approach: To examine trends regarding violence against women in Japan, Criminal Statistics and victimization surveys are employed. The utility of victimization surveys is demonstrated by the findings of the Survey of Women’s Safety in Daily Life, an international victimization survey that was conducted in Japan in 2016. Findings: This study arrived at the following three findings: (1) the prevalence of violence against women in Japan has remained relatively stable or declined over the past two decades; (2) the lack of standardization in the questions and data collection methods employed across victimization surveys represents a significant challenge to accurately estimating changes in victimization rates over time; and (3) it is anticipated that women in Japan are inclined to tolerate violence perpetrated by their intimate partners and that such incidents remain largely unacknowledged in public discourse. Originality/value: The study utilized a victimization survey of women in Japan that was identical to a survey conducted in the European Union (EU). By comparing the results, the study was able to identify characteristics and problems regarding violence against women in Japanese society. In this way, this study makes a substantial contribution to the field of comparative criminology and victimology, such as its demonstration of the cultural divergences in police reporting practices.